1997
DOI: 10.1023/a:1006524321335
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Metastatic rat colon cancer cells but not normal rat hepatocytes showed activity of cathepsin B on their plasma membranes. Activity was visualized in living cells with a new fluorogenic substrate, [Z-Arg]2-cresyl violet, and confocal microscopy. When these cancer cells were injected into the portal vein of rats, the animals developed tumors in the liver in a heterogeneous fashion. Three- to four-fold more tumors were found in the small caudate lobe than in the other three large lobes of the liver. Oral treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…2c). Next, to visualize the subcellular sites of cathepsin L activity, we used a fluorogenic substrate CV-(FR) 2 , which emits fluorescence light upon cleavage by cathepsin L (36). In nontreated podocytes, we found a low baseline activity in lysosomes (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2c). Next, to visualize the subcellular sites of cathepsin L activity, we used a fluorogenic substrate CV-(FR) 2 , which emits fluorescence light upon cleavage by cathepsin L (36). In nontreated podocytes, we found a low baseline activity in lysosomes (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Fluorescence was recorded every 10 min for 1 h using a Wallac fluorometer with a 355-nm excitation filter and a 460-nm emission filter. Cathepsin L activity in living cells was visualizing with cresyl violet as a substrate (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that cathepsin B not only degrades components of the ECM such as laminin, collagen, and ®bronectin and structures of basement membranes (Buck et al, 1992), but also activates other proteolytic enzyme systems (Kobayshi et al, 1993;Schmitt et al, 1992). A recent study has shown that inhibition of extracellular cathepsin B inhibits the growth and metastasis of rat colon cancer cells (Van Noorden et al, 1998), providing further evidence for the involvement of cathepsin B in tumor invasion. Cells transfected with antisense cathepsin B cDNA exhibited a decrease in cathepsin B activity, which resulted in a reduced invasion and motility of treated cells (Krueger et al, 1999).…”
Section: Introductionmentioning
confidence: 86%
“…Examples are turnover alyzed quantitatively in individual cells by capturing of collagen (7)(8)(9), activation of the immune system (10), series of images in time. Production of fluorescence arthritis (11,12), and metastasis of cancer (13,14). For strates for proteases containing cresyl violet was syn-Cresyl violet-dependent fluorescence appeared in a similar way when cells were analyzed by flow cytome-thesized.…”
mentioning
confidence: 99%